A semiquantitative and qualitative histopathologic assessment of the effect of type II intrauterine growth retardation on the structure of the carotid bodies in fetuses and neonates - Laing, David (Division of Anatomical Pathology, 2017)
The major physiological function of the carotid body is to respond to a low partial pressure of oxygen in the systemic arterial blood. The structure and functions of the adult carotid body have been extensively investigated over the past fifteen years. However, the carotid body in children has been relatively neglected with only a handful of studies being performed. To date, no study has been undertaken to investigate the effects of intrauterine hypoxia on the carotid body of foetuses. Clinically, intrauterine growth retardation has been ascribed, amongst other causes, to placental insufficiency that results in chronic hypoxia in the fetus. Intrauterine growth retardation can be divided into two types: - Type I (symmetrical) and type II (asymmetrical). In Type II intrauterine growth retardation, growth retardation does not become clinically evident until the third trimester. There is relative brain sparing with a greater deprivation in the size of abdominal organs, such as the liver and the kidneys. Previous studies have shown that there is no correlation between volume of the carotid body and hypoxia in children. However, Heath et al. made the observation that there are three variants of chief cells (progenitor, light and dark) within the carotid body and that an increase in the relative percentage of the dark subtype is an indicator of hypoxia. Using this observation, the present study set out to test two hypotheses: Firstly, whether the carotid body is functional in utero; and secondly whether there are any objective morphological changes in the carotid bodies of fetuses that have been subjected to intrauterine growth retardation. The carotid bodies from 72 fetuses with a gestational age between thirty and forty weeks were removed from the archived autopsy material, and differential cell counts were performed of the various cells present within the carotid bodies, using haematoxylin and eosin stained sections of the carotid bodies. The cases were assigned to three groups: - I) cases that had clinical and pathological evidence of intrauterine growth retardation, 2) negative controls and 3) positive controls. The three main groups were categorised as follows: -: (1) Intrauterine growth retardation (all cases with a weight for gestational age that is below the tenth centile and a brain to liver ratio of greater than four.) (2) Negative controls (all cases in whom there is a normal weight for age, a brain to liver ratio of less than three and no histological evidence of an episode of significant hypoxia before death). (3) Positive controls (all cases in whom there was clinically significant hypoxia present before death). The groups comprised of: 20 hypoxic positive controls, 15 negative controls, and 16 test cases which had suffered from intrauterine growth retardation. The remaining 21 cases were 7 dysmorphic infants, 3 congenital infection cases (congenital syphilis) and 11 cases that fitted the negative control criteria but had suffered significant hypoxia, thus excluding them from that category. The results showed that no significant difference was present in the percentage of sustentacular cells between any of the three groups. The results of the percentage of dark chief cells were as follows: l) mean percentage of dark chief cells in the intrauterine growth retardation group was 21.1 ±10.9%. 2) mean percentage of dark chief cells in the negative controls was 12.3 ±7.3%. 3) mean percentage of dark chief cells in the positive controls was 21.2 ±9.8%. A significant difference was present between the intrauterine growth retardation cases and the negative controls p=0.013, and between the positive and negative controls p=0.006. The dark chief cell count in the intrauterine growth retardation group showed no significant difference from the positive controls. No age-related difference appeared to be present in any of the groups. The conclusions reached are: a) Clinical hypoxia correlates with morphological changes in the carotid body, manifesting as an increase in the percentage of dark chief cells. b) intrauterine growth retardation cases show similar morphological changes in the carotid body to cases that have suffered from clinical hypoxia. c) therefore, by deduction intrauterine growth retardation fetuses have probably also been exposed to significant hypoxia while in utero. d) the fact that morphological changes in response to hypoxia are occurring in the carotid bodies of fetuses is an indication that the carotid body may be functional in utero. The results of the study indicate that a dark chief cell percentage of greater than 20% indicates that the fetus has been subjected to significant hypoxia, while a percentage of less than 10% indicates that it has not. A percentage of between 10 and 20% is unhelpful in determining whether hypoxia has taken place. The results of this study indicate that histological examination of the carotid bodies in neonates suspected of intrauterine growth retardation could be a useful additional means of assessment.